(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2024)
This article explores how courts derive implicit rights from explicit ones through judicial interpretation. Constitutions enumerate fundamental rights and liberties, but the language of the law, as a social construct, can often be vague. Utilizing the conceptual framework of the penumbra from Griswold v. Connecticut and HLA Hart’s core and penumbra theory, this article delves into the methods of judicial reasoning employed to derive implicit rights. Starting with a general outline of the penumbra concept, the study applies it to landmark cases from Nepal, where courts have derived implicit rights, and juxtaposes these with cases where no such derivations were made. The focus is on the method of judicial reasoning rather than an appraisal of the case outcomes. The key argument is that judges justify the derived implicit rights as inherent to explicit guarantees, rather than taking credit as “norm entrepreneurs.” Judges support their reasoning by appealing to a broader constitutional vision, emphasizing the inherence of implicit rights arising from a confluence of multiple rights, and broadly deferring to an international normative regime. The conclusion highlights that subsequent constitutional developments often transform implicit rights into explicit ones, reflecting a logical and systematic judicial approach that enhances the protection and clarity of fundamental rights. This systematic approach underscores the dynamic nature of constitutional law, where implicit rights are not static but evolve into explicit rights, thus progressively broadening the scope of protected fundamental rights and ensuring their effective implementation within the legal framework.